Valuing animal genetic resources in peasant economies: The case of the box keken creole pig in Yukatan - Riccardo Scarpa; Adam Drucker; Simon Anderson; Nancy Ferraes-Ehuan; Veronica Gomez (Fondazione Eni Enrico Mattei (FEEM), 2001)
We report the results of a choice-experiment study to model preferences over a selection of breed traits of 'creole' pigs. The study was conducted amongst households of backyard producers and small farmers rearing this local breed in Yucatan, Mexico. Hypothetical choice data were collected to estimate the preference of households over alternative pigs profiles whose attributes distinguish creole pigs from the potentially more productive, yet less adapted exotic breeds currently threatening to severely displace this locally adapted animal genetic resource. The observed choices are employed to estimate a series of random utility models whose results are tested for preference equality between households and small farmers. Stated-preference based estimates are found to be of the same magnitude as revealed-preference producers costs. As a consequence the method is deemed to be appropriate for the valuation of non-market functions in production. Estimates conditional on household characteristics are then presented and discussed.
Keywords: 330; Biodiversity values; genetic resources; stated preference; choice experiments; livestock values; non-market values; creole pig; Artenvielfalt; Bewertung; Schwein; Tierzucht; Yucatán